Sensory World - Introduction to Sensation and Perception - Bennett,tl - Fineman, MB (Contemporary Psychology, 1979)
Keywords: dept.psy; ⛔ No DOI found

Premorbid Social Competence and Outcome among Schizophrenic and Nonschizophrenic Patients - Zigler, Edward; Glick, Marion; Marsh, Anna (The Journal of Nervous and Mental Disease, 1979)
The relation between premorbid social competence and outcome was examined with 381 male state hospital patients in four diagnostic categories: schizophrenia, affective reaction, psychoneurotic disorder, and personality disorder. Outcome was assessed using the measures of length of initial hospitaliz
Keywords: Affective Symptoms; Hospitals, Psychiatric; Human; Length of Stay; Male; Neurotic Disorders; Outcome and Process Assessment (Health Care); Personality Disorders; Prognosis; Schizophrenia; Schizophrenic Psychology; Social Adjustment; Support, U.S. Gov't, P.H.S.; affective neurosis; central nervous system; dept.psy; hospitalization; major clinical study; neurosis; personality disorder; schizophrenia; sociology; therapy